Pergeseran Budaya Permainan Anak di Aceh ( Suatu Tinjauan Sosiologis Antropologis) - Asmanidar, Asmanidar (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2017)
The changable of the Acehness kids playing is a social and cultural change from time to time. It might be been seen from the anthusiastic of society in fulfilling the toys to the kids from traditional playing such as gaseng, geunteut, cato, me-eun karet, me-eun chee, me-eun jambo-jamboan, dan patok lele to modern playing such as play station, laptop/computer, tablet, smartphone, game online etc. Here, we can compere that the traditional tools or toys playing are generally very simple, easy to find and no need to waste of money to get it, unically, it could be created by the player himself/herself. Otherwise, the modern toys playing, the kids have to spend much money to find it.This situation has a littel bit trouble to the parents who don’t have much money, while the kids need it as their friends had. We realize that both traditional and modern playing have positif and negatif effects to the kids themselves. The changables sometime are very slow motion, even so, these are very influence toward the kids mentality in the future.